International collaboration for the advancement of Entrepreneurship Education: An activity theory approach - America, C.; Neethling, A. (South African Journal of Higher Education, 2023)
Despite the prevalence of entrepreneurship studies across various levels of the education sector, the gap between theory and practice in entrepreneurship education is an ongoing pedagogical challenge. This is no exception in teacher education specifically, with regard to how and what we teach to cultivate entrepreneurial awareness. This article illustrates how an international collaborative online entrepreneurship initiative addresses this theory-practice gap underpinned by Engeström’s (2015) account of the transition from individual actions to collective activity. The research design is an interpretative, qualitative analysis based on the theoretical framework of activity theory, suggesting that motivation is necessary to spur on human behaviour and that motivation is prompted by objects (Engeström 1987; 1999). The collaborative interactions of the participants, who are South African student teachers, Dutch business management students, and a project facilitator, signify a flow of interactions that emerged from the activities within a system. Five key themes emerged: 1) technological intervention, 2) the impact on students 3) entrepreneurship framework, 4) system and stakeholders, 5) roles and tasks, and 6) instructional tools and pedagogy. This study suggests that even with dedicated teachers, a collaborative mentorship initiative can add value to increase entrepreneurial awareness. Furthermore, student teachers can play a valuable role in cultivating entrepreneurial thinking, but the development and synchronization of such initiatives requires proficient facilitation. This article further illustrates that efficient facilitation of local and international collaboration holds potential for the further expansion of entrepreneurship education within teacher education, which could then be cascaded to the school system.